2016
DOI: 10.4236/ajps.2016.71022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity of NIFOR Oil Palm Main Breeding Parent Genotypes Using Microsatellite Markers

Abstract: The genetic diversity among 15 NIFOR breeding parents was assessed using 10 microsatellite markers. A high genetic diversity was observed with a total of 64 alleles including 23 rare alleles or alleles at frequencies less than 0.05. The NIFOR tenera parents recorded the highest number of rare alleles. The average observed heterozygosity and mean gene diversity across all parental groups were 0.6889 and 0.7029, respectively. Higher genetic diversity was detected among the NIFOR dura and tenera parents compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
1
10
0
3
Order By: Relevance
“…and SCoT markers were higher than 0.345 and 0.298 when ISSR markers were used for the analysis on Vigna radiata and Vigna subterranea accessions. The PIC values identified in this study revealed that ten of the ISSR markers were able to identify the genetic diversity between the different oil palm progenies, which is in agreement with the study of Okoye et al (2016) which reported that the PIC values generated by SSR markers were helpful in the assessment of the diversity inequity between genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…and SCoT markers were higher than 0.345 and 0.298 when ISSR markers were used for the analysis on Vigna radiata and Vigna subterranea accessions. The PIC values identified in this study revealed that ten of the ISSR markers were able to identify the genetic diversity between the different oil palm progenies, which is in agreement with the study of Okoye et al (2016) which reported that the PIC values generated by SSR markers were helpful in the assessment of the diversity inequity between genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…This value is similar to that reported by Khierallah et al (2011), who evaluated the genetic diversity of 30 oil palm cultivars with 22 microsatellite markers, finding a high level of polymorphism and an expected heterozygosity of 0.503 for all cultivars. Okoye et al (2016a) reported high heterozygosity and genetic diversity values of 0.69 and 0.70, respectively, when studying genetic diversity among NIFOR (Nigerian Institute For Oil palm Research) palm parentals with 10 microsatellite markers. Okoye et al (2016b) found average values of observed and expected heterozygosity of 0.63 and 0.76, respectively, when studying the genetic relationships between 26 oil palm materials from Nigeria and Malaysia with nine microsatellite markers.…”
Section: Resultsmentioning
confidence: 99%
“…PIC values also was used to find the informative primers to see diversity. The PIC of RAPD have a maximum value of 0.5 [2]. A good RAPD primer can show a high percentage of polymorphic and a high score of PIC [23].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variance can be seen according to value of heterozygosity and value of homozygosity. If the value of heterozygosity is higher than the value of homozygosity, so that the genetic variance is high [2] [3]. If genetic variance between wild population compare with commercial oil palm can be found there were genetic depression.…”
Section: Introduction Il Palm (E Guineensis ) Is a Species From Fmentioning
confidence: 99%